2017
DOI: 10.1002/2017ja024602
|View full text |Cite
|
Sign up to set email alerts
|

First Study on the Occurrence Frequency of Equatorial Plasma Bubbles over West Africa Using an All‐Sky Airglow Imager and GNSS Receivers

Abstract: This is the first paper that reports the occurrence frequency of equatorial plasma bubbles and their dependences of local time, season, and geomagnetic activity based on airglow imaging observations at West Africa. The all‐sky imager, situated in Abuja (Geographic: 8.99°N, 7.38°E; Geomagnetic: 1.60°S), has a 180° fisheye view covering almost the entire airspace of Nigeria. Plasma bubbles are observed for 70 nights of the 147 clear‐sky nights from 9 June 2015 to 31 January 2017. Differences between nighttime an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
2
12
0
Order By: Relevance
“…In the case of the West African sector, past studies (Okoh et al, 2017;Yizengaw et al, 2013) have presented a similar discussion about the role of GW in the observed large RSF occurrence during a solstice month. Yizengaw et al, (2013) attributed the post-midnight enhancement of the eastward polarization electric field in the West African region to the presence of the localized charged particle.…”
Section: Discussionmentioning
confidence: 63%
“…In the case of the West African sector, past studies (Okoh et al, 2017;Yizengaw et al, 2013) have presented a similar discussion about the role of GW in the observed large RSF occurrence during a solstice month. Yizengaw et al, (2013) attributed the post-midnight enhancement of the eastward polarization electric field in the West African region to the presence of the localized charged particle.…”
Section: Discussionmentioning
confidence: 63%
“…The influence of solar and magnetic cycle is also studied. Magdaleno et al [42] studied the Climatology characterization of EPB using GPS data for the period 1998-2008. They have considered the slant total electron content (sTEC) derived from global positioning system (GPS) data from 67 International GNSS Service (IGS) stations distributed worldwide around the geomagnetic equator and the region of the ionospheric equatorial anomaly (IEA).…”
Section: Equatorial Plasma Bubble By Gpsmentioning
confidence: 99%
“…First time study of the occurrence frequency of EPB over West Africa is done by Okoh et al [42] using an ASI and GNSS Receivers from June 9, 2015 to January 31, 2017. This ASI is installed at Abuja (Geographic: 8.99°N, 7.38°E; Geomagnetic: 1.60°S) which covers almost the entire airspace of Nigeria.…”
Section: Equatorial Plasma Bubble By Gpsmentioning
confidence: 99%
“…V p plays a significant factor in describing and specifying many ionospheric models across the globe. It has also been found to be a significant factor in the manifestation of plasma bubbles and Equatorial Spread-F [1,2,3,4] through the action of the evening-time Pre-reversal enhancement (PRE) activity. The PRE is the evening-time enhanced E x B drifts driven by the eastward electric field., and consequently lifts the ionosphere.…”
Section: Introductionmentioning
confidence: 99%